Electronic Health Record in the ICU: An Essential Need in the Modern Era - M, Bolaki; I, Papakitsou; V, Mavrikaki; E, Kondili (Archives of Case Reports, 2023)
One of the most significant changes in modern healthcare delivery has been the evolution of the paper record to the electronic health record (EHR). Despite incentives that provide reimbursements to hospitals and healthcare providers for adopting EHR technology, there is a large number of barriers that preclude its implementation. EHR has a great impact on a variety of healthcare outcomes, mainly favoring its use. Consequently, the development of effective implementation strategies is essential in modern healthcare society.